Responses of Free-Living Vibrio Community to Seasonal Environmental Variation in a Subtropical Inland Bay - Chen, Xing; Zhao, Huaxian; Jiang, Gonglingxia; Tang, Jinli; Xu, Qiangsheng; Huang, Lengjinghua; Chen, Si; Zou, Shuqi; Dong, Ke; Li, Nan (Frontiers in Microbiology, 2020)
Vibrio are widely distributed in aquatic environments and strongly associated with eutrophic environments and human health through the consumption of contaminated seafood. However, response of Vibrio community to seasonal variation in eutrophic environments is poorly understood. In this study, we used a Vibrio-specific 16S rRNA sequencing approach to reveal the seasonal distribution pattern and diversity of the Vibrio community in the Maowei Sea, Beibu Gulf of China. Shannon diversity of the Vibrio community was highest in summer, while β-diversity analysis showed that Vibrio community structures were significantly different between seasons. Distance-based redundancy analysis (dbRDA) and Mantel test analysis suggested that total dissolved nitrogen (TDN), total dissolved phosphorus (TDP), dissolved inorganic nitrogen (DIN), salinity, and temperature were the key environmental factors shaping Vibrio community structure, indicating a strong filtering effect of trophic condition on the Vibrio communities. Furthermore, through random forest analysis, V. fluvialis, V. alginolyticus, V. proteolyticus, V. splendidus and the other eight Vibrio species were more sensitive to the eutrophic changes. This study revealed seasonal changes in Vibrio communities and the influence of environmental variation on Vibrio community composition, contributing to a better understanding of their potential ecological roles in subtropical inland bay.